Kinetic Analysis of Phenol Biodegradation by Isolated Bacteria and Mixed Culture by Cells Immobilized on Loofa (Lugga Cylindrica) Sponge in Airlift Bioreactior - Faisal Faisal; Yasunori Tanji; Hajime Unno (ASEAN Journal of Chemical Engineering, 2003)
Varios contaminated soil samples were examined for isolation of microorganisms responsible for phinol degradation. One type pure culture gram positive bacterua was isolated and identified as Bacillus pulvifaciens. isolated bacteria and an activated sludge were acclimated for 75 days to a medium containing phenol is a speratae 250 ml Erlenmeyer flasks. After this period of time, biomass was transferred into airlift bioreactor with looga sponge for cells immobilization and acclimation which was operated by fill and draw moder faro 70 days. The immobilized cells gres wthin the void space of the loofa spongem reaching a high cells concentration of 21.4 g-calees/l-sponge volume and the free cells in the effluent became arround of 0.7 g/l. The performance of airlift bioreactir for 27 hours operation after acclimation period, showed that decrease in phenol concentration after 24th hour culture with isolated bacteria and the activated sludge culture were 99.8% and 84,2% removal, respectivaly. The phenol and COD degradation by the isolated bacteria was higher than that of the activated sludge culture. Based on the experimental data, kinetic model was discussed. through the model the biokinetic paramters were evaluated, which represented the behavior of eractor very well.